Flashing boobies and naughty no-no’s: a media-historiographical overview of the pornographic magazine in South Africa, 1939 to 1989 - Boonzaier, Christiaan Nicolaas (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)-- Stellenbosch University, 2014.